Spot indole test: evaluation of four reagents. - Miller, J M (1982)
Kovacs indole reagent, p-dimethylaminobenzaldehyde, Ehrlich indole reagent and p-dimethylaminocinnamaldehyde were used as spot indole reagents to test 359 strains of gram-negative rods growing on 5% sheep blood agar, Trypticase soy agar (BBL Microbiology Systems), and MacConkey agar. The p-dimethylaminocinnamaldehyde reagent was the most sensitive of those tested and provided results that were easiest to interpret. The p-dimethylaminocinnamaldehyde reagent was able to detect providencia alcalifaciens indole production because of the red-violet color unique to that organism. All reagents tested were accurate in detecting indole produced by members of the Enterobacteriaceae family, with the exception of P. alcalifaciens.